A Systematic Review of Social Maintenance Behavior Outcomes of Interactive Social Interventions for Children With Autism Spectrum Disorders. (June 2021) - Short, Cassie Ann; Vital, Pedro
A large and varied evidence base supporting the efficacy of social therapies to improve the social behaviors of children with autism spectrum disorders (ASD) does not permit a clear understanding of which specific types of social behavior are improved by specific social therapies. Social maintenance behaviors function to form and sustain relationships, which has been associated with a reduction in negative social experiences in children with ASD. The present systematic review investigates the effectiveness of interactive social therapy in increasing these specific behaviors in this population. A systematic search of PsycArticles, Medline, Education Resources Information Centre, Child Development and Adolescent Studies, and Scopus databases identified 18 articles as relevant for inclusion. The extant evidence suggests that interactive social therapies are effective in increasing social maintenance behaviors in children with ASD. Explicit targeting of these behaviors and inclusion of reinforcement are highlighted as potentially active components in this regard.